Self Generated Snow Dust. Trajectory prediction of snow particles generated from the car. - Tan, Jian (Chalmers tekniska högskola / Institutionen för tillämpad mekanik, 2015)
When a car is running on a snowy road, the snow on the ground can be lifted up as snow particles and these lifted particles can flow around the car. In this project, Computational Fluid Dynamics(CFD) method will be applied to study, simulate and replicate this specific phenomena. With the help of the test work, which has been done previously at Jokkmokk Proving Ground(JPG), there is a certain amount of experimental test data available, including precipitation of particles at different location, video logs and other environment information. The precipitation data will be the goal for the numerical simulation to reach, which is a validation of this method development. The numerical simulation to predict the particle trajectory and distribution of precipitation is done using CFD technique with multiphase flow approach. Both the experimental data and numerical predictions are presented, interpreted and discussed. It turns out that this method can partly replicate the experimental data, while there are certain specific phenomena that cannot be simulated or reflected from the numerical prediction. This report begins with introduction of problem and aim. The implementation is described with motivations after the theory section. Results with discussions are presented after the implementation method. Possible improvements and future work are also recommended.